TMOD-32. GL261 LUCIFERASE-EXPRESSING CELLS ELICIT AN ANTI-TUMOR IMMUNE RESPONSE: AN EVALUATION OF MURINE GLIOMA MODELS. (11th November 2019) - Sanchez, Victoria; Lynes, John; Walbridge, Stuart; Wang, Xiang; Edwards, Nancy; Nwankwo, Anthony; Dominah, Gifty; Obungu, Arnold; Adamstein, Nicholas; Dagur, Pradeep; Wu, Tianxia; Maric, Dragan; et al.
Abstract: Preclinical models that reliably recapitulate the immunosuppressive properties of human gliomas are essential to assess immune-based therapies. Intracranially injected GL261 cells are widely used as an immunocompetent animal model of glioma, but it is common practice to transfect these with luciferase to facilitate tumor monitoring during treatment. Our group has previously shown that the luciferase-expressing GL261 Red-FLuc cells create an inflammatory response when implanted intracranially. Now, we additionally explore the inflammatory response of GL261-Luc2 cells and demonstrate a similar host immune response occurs with this model as well. In our in vivo evaluation, C57BL/6 mice underwent stereotaxic, intracranial implantation with GL261, GL261 Red-FLuc or GL261-Luc2 cells at doses of 5x10 4 cells/5mL or 3x10 5 cells/5uL.MRIs were performed to monitor relative tumor growth. To assess intrinsic differences between cell lines, in vitro cytokine profiles were evaluated by proteome microarray. Kaplan-Meier survival analyses demonstrated median survival for mice implanted with GL261 cells at 5x10 4 cells was 18 to 21 days. The GL261-Red FLuc implanted mice cells did not reach median survival at either tumor dose with greater than 60% of mice termed long-term survivors. Finally, mice injected with GL261-Luc2 cells at 3x10 5 cells reached median survival at 23 days, but median survival was significantly prolonged for mice implanted with GL261-Luc2 at a dose of 5x10 4 cells (37 days, with 40% becoming long-term survivors) compared to GL261 implanted mice. MRIs reveal differences in tumor growth that correspond with the differences in median survival between groups. In addition, proteomic analyses revealed significantly elevated inflammatory cytokines such as IFN-gamma, IL-7 and TNF-alpha in the supernatants of the GL261 Red-FLuc cells and GL261-Luc2 cells. Further immune characterization is ongoing. Our data suggests that GL261 Red-FLuc and GL261-Luc2 murine models elicit an anti-tumor immune response by increasing pro-inflammatory modulators which stimulate the tumoricidal function of immune cells in the tumor microenvironment.